Yogurt Consumption and Purchasing Reasons among Consumers in Kuching, Sarawak - Myat Su, Bo; Cheah, Whye Lian; Siti Khadijah bt, Joha; Nur Ad'lina, Mahammad; Issac Evan, Jolly; Darshika Tamil, Selvan (UNIMAS Publisher, 2022)
Yogurt provides the body with nutrients such as vitamin B, minerals and proteins. Despite the nutrition offered by yogurt, local studies in Malaysia reported that the consumption of yogurt still remains as one of the lowest amongst all dairy products in Malaysia. This study was conducted to determine the yogurt consumption and purchasing reasons among yogurt consumers in Kuching, Sarawak. It was a descriptive study based on online survey via Google form. Respondents were recruited from a list of customers of a yogurt supplier in Kuching via an advertisement through social media. Data was analysed using IBM SPSS (version 27). A total of 236 respondents participated in this study whereby the majority were females (71.2%) and most of respondents bought their yogurt from being informed by advertisement. A majority used yogurt at least once a month and most likely type of yoghurt used was the yoghurt drink (61.9%). The largest share of respondents indicated that the quality of product (93.7%), variation in flavour (83.9%), information in product’s label (79.7%), price consideration (71.2%), quality (71.2%), ease of location (76.2%) and access of transportation (69.9%) markedly stimulated their consumption behaviour in finalising their yogurt purchasing reasons. Consumer’s behaviour toward the yogurt purchasing decision were controlled specifically by its product factors, prices offered and accessibility of conditions. Implications of this study have contributed to future local research on population study in the Sarawak and may increase the awareness of yogurt’s benefits among non-yogurt buyers to encourage greater consumption.